Oxidative status and stress during highly energetic life-history stages of Chinstrap Penguins: breeding versus molting - Colominas Ciuró, Roger; Masero, José A.; Benzal, Jesús; Bertellotti, Néstor Marcelo; Barbosa, Andrés (Journal of Field Ornithology)
Life-history stages such as reproduction and molt are energetically costly. Reproductive costs include those associated not only with offspring production, but also protecting and provisioning young. Costs typically associated with molting include decreased thermoregulatory and locomotive performance, and increased metabolic and nutritional costs. Energetic demands may disrupt homeostasis, particularly in terms of its maintenance (e.g., oxidative stress and immunity). Few investigators have explored the relationship between effort (increased metabolic rate) and oxidative status and stress by comparing life-history stages with different energetic demands. However, comparative studies are crucial for understanding the processes of energy allocation and their consequences for different physiological functions. Our objective was to determine how two highly demanding life-history stages, breeding and molting, affected oxidative balance in Chinstrap Penguins (Pygoscelis antarcticus), a species where these two activities do not overlap. We found that the heterophil/lymphocyte (H/L) ratio was significantly higher during breeding than molting; oxidative damage was also higher during breeding. In contrast, we found no significant differences between these stages in total antioxidant capacity. We also found sex differences, with males having greater oxidative damage than females. Our results suggest that breeding is more stressful and more demanding for Chinstrap Penguins than molting, and provide further support for the relationship between effort, in terms of increased metabolic rate, and oxidative balance. Fil: Colominas Ciuró, Roger. Consejo Superior de Investigaciones Cientificas. Museo Nacional de Ciencias Naturales; España Fil: Masero, José A. Universidad de Extremadura; España Fil: Benzal, Jesús. Consejo Superior de Investigaciones Científicas. Estación Experimental de Zonas Aridas; España Fil: Bertellotti, Néstor Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico ...